2018
DOI: 10.4103/jets.jets_112_17
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Profile and its Utilization in Head Injury Patients in Emergency Department: A Prospective Observational Study

Abstract: Context:Based on Glasgow Coma Scale (GCS), head injury can be classified as minor (GCS 13–15), moderate (GCS 9–12), and severe (GCS 3–8). There is a lot of controversy in the use of computed tomography (CT) in head injury patients.Aims:This study was intended to estimate the rate of CT positivity in head injury patients and to define the criteria for doing CT in head injury patients.Settings and Design:This was a prospective observational study in the emergency department (ED) over a 12-month period. Subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…These primary injuries include intracranial hemorrhages, contusion, traumatic axonal injuries, scalp injuries, and fractures. 2 5 11 Detection of the latter, especially when involving the base of the skull, is the significant feature of CT. This is further facilitated with the exploit of bone algorithm CT or three-dimensional (3D) volumetric CT. CT, therefore, has become the consensus choice as it has a rapid imaging time, high sensitivity for calvarial fracture detection, and high potential for the detection of lodged radiopaque foreign bodies.…”
Section: Introductionmentioning
confidence: 99%
“…These primary injuries include intracranial hemorrhages, contusion, traumatic axonal injuries, scalp injuries, and fractures. 2 5 11 Detection of the latter, especially when involving the base of the skull, is the significant feature of CT. This is further facilitated with the exploit of bone algorithm CT or three-dimensional (3D) volumetric CT. CT, therefore, has become the consensus choice as it has a rapid imaging time, high sensitivity for calvarial fracture detection, and high potential for the detection of lodged radiopaque foreign bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Low threshold for taking CT is advisable in elderly and alcohol-intoxicated patients. In mild head injury, CT has indicated if any one of the following risk factors is present: loss of consciousness (LOC >5 min), history of vomiting, history of seizures, history of ear bleed, and history of nosebleed 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The present study examines the role of computed tomography (CT) scan in patients with traumatic brain injury and discusses the demographic details, injury distribution, intracranial imaging findings, and identifies the risk factors to request a CT scan in patients with suspected traumatic brain injury (TBI). [ 1 ] It is beyond doubt that the CT is rapid, widely available, and one of the most valuable imaging modality to investigate patients with TBI in the emergency department. [ 2 ] The use of CT scan in the emergency department has been progressively increasing[ 3 4 5 6 ] which not only has the potential to increase the cost of care[ 7 8 ] but also the increased radiation exposure can lead to a harmful sequel.…”
mentioning
confidence: 99%
“…[ 3 9 10 11 ] This study clearly identifies that CT is indicated in all patients with moderate and severe head injury (Glasgow Coma Scale ≤12), and there should be low threshold for asking a CT scan in elderly and in patients who are under influence of alcohol. [ 1 ]…”
mentioning
confidence: 99%
See 1 more Smart Citation